Judgement of Children’s Home Youths on Good and Bad (Training and Practice : Journal of Educational Sciences, 2017)
The moral evolution of the human beings reaches the point where they are able to make autonomous decisions at school age. Delightful and traumatic experiences of childhood shape an individual's perception of "good" and "bad", so by fourteen years of age they can argue for their personal judgements. But how does the moral progression form in the personalities of children raised in children's homes? How does hurtful parenting influence their confidence? How does the system which takes them out of their families guide them? How do the less impulsive institutional atmosphere and the constant seclusion from their peers influence them? I intend to answer these questions with structured interviews. The interviewees were young adults between the age of 14 and 18 who were forced to decide who is good and bad based on multiplied cases of traumatizing situations in life.